Nuevos registros y actualizaciones de Iviraiva argentina (Hersiliidae) para Argentina - Giambelluca, Luis Alberto (2021)
Spiders of the Hersiliidae family are easily distinguishable from others by the presence of a pair of long, posterior, lateral spinners that they use to capture prey. In Argentina, there are two genera Ypypuera and Iviraiva. In the present paper, new locations are provided for Iviraiva argentina and the historical records of this species for Argentina are reviewed, correcting georeferencing errors cited in the literature. The new records, being the southernmost for America, and the updated information, highlight the importance of accurate distributional data.